INCREASING THE EFFECTIVENESS OF PERSUASIVE COMMUNICATION THROUGH THE USE OF EMOTIONAL INTELLIGENCE - Fatih Humam Ramadhan; Dian Adriany (Publikasi Indonesia, 2023)
Persuasive communication is a form of communication that aims to influence the attitudes, beliefs, and behavior of the audience. However, the effectiveness of persuasive communication depends on the communicator's ability to convey the message persuasively and convincingly. Emotional intelligence is an individual's ability to recognize, understand, and manage one's own emotions as well as the emotions of others. This study aimed to examine the effect of the use of emotional intelligence on the effectiveness of persuasive communication. This study used an experimental method with a pretest-posttest control group design. The study participants consisted of 60 college students who were randomly divided into experimental groups and control groups. The experimental group was given emotional intelligence training for 3 days, while the control group was not given training. Afterwards, both groups were asked to make persuasive presentations on controversial social issues. Assessment of the effectiveness of persuasive communication is carried out by an independent jury. The results showed that there was a significant difference between the effectiveness of persuasive communication of the experimental group and the control group. The experimental group produced a more persuasive and convincing presentation compared to the control group. This suggests that the use of emotional intelligence can increase the effectiveness of persuasive communication. This research has important implications for persuasive communication practitioners, especially in terms of training and developing persuasive communication skills. Emotional intelligence training can improve communicators' ability to recognize audience emotions, understand their needs and wants, and manage their own emotions in persuasive communication situations